DETERMINAN AGRESIVITAS PAJAK PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rahma Syawari Mustika, 12.05.52.0045; Maryono, Maryono (Students' Journal of Accounting and Banking, 2016)
This study aimed to analyze the effect of firm likuidity, leverage, independent commissioner, audit committe, and size to aggressiveness taxes. The object of this study is on the Mining Company listed on the Indonesia Stock Exchange (IDX) 2010-2014. The sampling method used is purposive sampling the study period of 2010 throuhgt 2014. The data analysis technique used is multiple linear regression. The results of this study indicate that the hypothesis testing showed that the variable Liquidity and Independent Commissionerhad positive effect and no significant to the Aggressiveness Taxes. Whereas Leverage, Audit Commite and Size has positive effect and significant on Aggressiveness Taxes.Keywords: Liquidity, Leverage, Independent Commissioner, Audit Committe, Size, Aggressiveness Taxes